Study of the factors associated with stillbirth in pregnant women admitted in Imam Reza Teaching Hospital in Kermanshah (2011-2014) - Anisodowleh Nankali; maryam hematti; Zakaria Mahdavi (Mashhad University of Medical Sciences, 2017)
Introduction: Stillbirth is a devastating pregnancy outcome and is often defined as fetal death after 20 weeks of gestation. Annually, 2.6 million stillbirths occur worldwide, 98% in developing countries. It is crucial that we understand the causes and contributing factors. This study was performed with aim to evaluate the factors associated with stillbirth in pregnant women admitted in Imam Reza Teaching Hospital in Kermanshah, Iran (2011-2014). Methods: This descriptive study was performed on 423 cases of stillbirth in Imam Reza Teaching Hospital in Kermanshah during 2011-2014. Demographic data and target variables such as fetal, maternal, placental, amniotic fluid, uterine, trauma, and causes were recorded in data collection forms. Data were analyzed by SPSS software (version 16). Results: Among 15376 births, 423 cases of stillbirth (2.75%) were registered. The causes of stillbirth were as follows: 117 cases (27.66%) fetal problems with the most frequency in gestational age of less than 27 weeks, 21 (4.96%) umbilical cord problems with the most frequency at 27-34 weeks of gestation, 68 (16.07%) placental problems with the most frequency  at 27-34 weeks of gestation, 147 (34.75%) amniotic fluid problems with the most frequency in less than 27 weeks of gestation, 42 (9.93%) uterus problems with the most frequency in more than 34 weeks of gestation, 149 (35.22%) maternal problems with the most frequency in less than 27 weeks of gestation, 42 (9.93%) due to trauma and often in less than 27 weeks of gestation, and 73 (17.26%) were classified as unknown. Conclusion: The maternal, fetal and amniotic fluid problems were the most cause of stillbirth and it is required to be paid more attention in prenatal care.